2016
DOI: 10.3171/2015.9.spine15628
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid scaffold has a neuroprotective effect in hemisection spinal cord injury

Abstract: OBJECTIVE Spinal cord injury occurs in 2 phases. The initial trauma is followed by inflammation that leads to fibrous scar tissue, glial scarring, and cavity formation. Scarring causes further axon death around and above the injury. A reduction in secondary injury could lead to functional improvement. In this study, hyaluronic acid (HA) hydrogels were implanted into the gap formed in the hemisected spinal cord of Sprague-Dawley rats in an attempt to attenuate damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Previous studies also showed that HA with high molecular weight was an essential organizational and structural component in the native brain ECM and had neuroprotective effects. 71,72 However, no discernible neurite outgrowth was generated in our Me-HA hydrogels. Instead, single hiPSC-NPCs spontaneously migrated and accumulated in dispersive sphere-like circular islands.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies also showed that HA with high molecular weight was an essential organizational and structural component in the native brain ECM and had neuroprotective effects. 71,72 However, no discernible neurite outgrowth was generated in our Me-HA hydrogels. Instead, single hiPSC-NPCs spontaneously migrated and accumulated in dispersive sphere-like circular islands.…”
Section: Discussionmentioning
confidence: 84%
“…A rat model of sciatic nerve crush is commonly used to study the cellular and molecular mechanisms in the peripheral nerve, 30 reported that HMW-HA has neuroprotective, 31,32 antioxidants, 33 and antiinflammatory 7,34 properties, which is believed that a variety of pharmacological actions of HMW-HA might contribute to its beneficial effect on axonal regeneration by suppressing the neuroinflammatory response. Even though our results showed the beneficial effect of HMW-HA on the injured sciatic nerve, data regarding the molecular mechanisms were limited in the current study.…”
Section: F I G U R Ementioning
confidence: 99%
“…[8][9][10] To mimic the stiffness of native nerve extracellular matrix (ECM), a variety of hydrogels with mechanical properties that can be tuned to be similar to those of native nerve tissue have been investigated as ideal candidates for spinal cord regeneration, showing positive roles in inducing stem cell neurogenic differentiation in vitro and axonal regrowth in vivo with significant and long-lasting motor functional recovery. [11][12][13][14][15][16][17][18][19] Unfortunately, most of these hydrogels are isotropic in architecture and lack oriented topography. Spinal cord tissue, especially the white matter that is composed of well-aligned axon tracts, has hierarchically oriented tissue structures ranging from a single neural axon to nerve fibers.…”
Section: Introductionmentioning
confidence: 99%